A statistical measurement of the H I spin temperature in DLAs at cosmological distances - Allison, JR (Oxford University Press, 2021)
Evolution of the cosmic star formation rate (SFR) and molecular gas mass density is expected to be matched by a similarly strong evolution of the fraction of atomic hydrogen (H I) in the cold neutral medium (CNM). We use results from a recent commissioning survey for intervening 21-cm absorbers with the Australian Square Kilometre Array Pathfinder (ASKAP) to construct a Bayesian statistical model of the NH I-weighted harmonic mean spin temperature (Ts) at redshifts between z = 0.37 and 1.0. We find that Ts ≤ 274 K with 95 per cent probability, suggesting that at these redshifts the typical H I gas in galaxies at equivalent DLA column densities may be colder than the Milky Way interstellar medium (Ts, MW ∼ 300 K). This result is consistent with an evolving CNM fraction that mirrors the molecular gas towards the SFR peak at z ∼ 2. We expect that future surveys for H I 21-cm absorption with the current SKA pathfinder telescopes will provide constraints on the CNM fraction that are an order of magnitude greater than presented here.